Electrocatalysis of oxygen reduction at electrodeposited molybdenum phosphate-based films - Luque, Gisela Carina (2012)
This work reports an electrode material containing molybdenum phosphate that shows a very interesting behavior as an electrocatalyst for the reduction of oxygen to water (ORR) in acid medium. The material is electrodeposited on a glassy carbon electrode from a solution of Mo(VI) and Co(II) in phosphate buffer at pH = 7. Cobalt is required to obtain a compact and uniform film. It is a non-crystalline solid conformed by metal oxide and phosphate groups that, according to XPS analysis, contains mostly Mo(VI) and a small fraction of Mo(V). Even though most of the Co-containing phase dissolves in acid, the film keeps its integrity and shows stable ORR activity in acid at very low overpotentials (from -0.3 V). The observed current density reaches a very small limiting value (∼2 μA cm -2) that is independent of the mass-transport conditions and could be associated to the small fraction of Mo(V) centers that function as ORR active sites. Although the film is thermally stable up to temperatures of 400 °C, by heating the material at temperatures above 100 °C it looses its unusual ORR activity due to the complete oxidation of Mo(V) to Mo(VI).